2004
DOI: 10.1007/s10843-004-0146-6
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Internationalisation: A Study of Entrepreneurial New Ventures in New Zealand

Abstract: This paper presents the findings of a study of the perceptions of the barriers to internationalisation by 561 New Zealand Entrepreneurial New Ventures (ENVs). Significant differences in the perception of the barriers are identified according to the level of international activity of New Zealand ENVs. Exporters and likely exporters consider the main barriers to internationalisation to be finance and cost-related factors. A lack of New Zealand government incentives are also seen to be major barriers for these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 36 publications
(51 reference statements)
5
121
0
1
Order By: Relevance
“…Many firms, particularly smaller firms, rely heavily on market-led innovations for success in international markets. Barriers to internationalisation differ somewhat by size and experience, with smaller less-experienced firms citing finance as the most significant (see also Shaw and Darrock, 2004). Larger firms with more experience are more concerned with market access, organisational systems and managerial capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many firms, particularly smaller firms, rely heavily on market-led innovations for success in international markets. Barriers to internationalisation differ somewhat by size and experience, with smaller less-experienced firms citing finance as the most significant (see also Shaw and Darrock, 2004). Larger firms with more experience are more concerned with market access, organisational systems and managerial capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al (1995), for instance, find just 22 percent of firms used more advanced modes involving overseas sales offices, joint ventures, and sales or production subsidiaries. Other studies have found even lower proportions of firms undertaking foreign direct investment (FDI) (4 per cent of manufacturing SMEs in Gerschewski"s (2005) study, 8 per cent in Shaw and Darrock (2004); 8 per cent in Bayfield et al 2009; also see Cooling, 1995;Bollard and Cremer, 1999;and Deloitte, 2008 for more on outward FDI by New Zealand firms). This exporting focus seems common to both traditional and emergent firms, as Chetty and Campbell-Hunt (2004a) conclude, that, most of their traditional counterparts, "born global" firms from New Zealand have not progressed to direct equity modes of internationalisation (ie.…”
Section: Entry Modesmentioning
confidence: 98%
See 2 more Smart Citations
“…Katsikeas et al (2000) evaluated more than 100 papers of pertinent empirical investigation to evaluated and to critique export performance measurements and provided some insights. Shaw and Darroch (2004) presented the findings of a comprehensive investigation on the perceptions of the barriers to internationalization by 561 New Zealand Entrepreneurial New Ventures (ENVs). They identified substantial differences in the perception of the barriers based on the level of international activity of New Zealand ENVs.…”
Section: Introductionmentioning
confidence: 99%